Conventional benefits: exclusivity of members or wage discrimination? - Martínez Rivera, Maria Isabel (2024)
This study discusses the challenges faced by the Peruvian judiciary when the pending controversies are related to Collective Law institutes. Although there are multiple edges and obstacles that surround collective labor relations, the purpose of this article is to expose the problems circumscribed to the beneficiaries of collective bargaining agreements resulting from minority unions, as well as the granting of conventional benefits to former service providers and CAS workers with a judicially recognized and subsequent relationship. In order to deepen in the analysis of such a robust subject, the author starts by breaking down historical, theoretical and normative aspects, referring to legal institutions of collective law and their significant presence in labor relations; in addition, she includes dissimilar pronouncements of the Peruvian Supreme Court of Justice, in order to know its position on the scope and extension of collective bargaining agreements. By means of the referred methodology, it concludes that extending the scope of action of benefits of a conventional nature (derived from negotiations of minority unions), to those who do not have the status of members, places the permanence of the union organization in a risky position.